Geochemical Tracing of Seabed Hydrocarbon Seepage in the Yantai Depression, South Yellow Sea Basin - Jianqiang Wang; Yuxi Zhang; Jian Zhang; Jie Liang; Qingfang Zhao; Heping Dong (Journal of Marine Science and Engineering, 2024)
Widespread submarine hydrocarbon seepage can form complex fluid seepage characteristics, with submarine sediment geochemistry effectively recording seepage activities and fluid component changes due to hydrocarbon seepage. This is crucial for offshore oil and gas exploration and understanding global climate change. Therefore, using the geochemical information of submarine sediments to trace hydrocarbon seepage activities is of great significance. In order to identify the geochemical anomaly characteristics and genetic types of acid-hydrolyzed hydrocarbons in submarine sediments in the Yantai Depression of the South Yellow Sea Basin, Eastern China, and to explore the relationship between these anomalies and deep oil and gas, geochemical columnar samples were taken at 100 stations in the study area. A total of 100 sets of acid-hydrolyzed hydrocarbon data and 26 sets of carbon isotope data were analyzed. The results show that the content of acid-hydrolyzed hydrocarbons at each station is in the following order: methane (AC1) > ethane (AC2) > propane (AC3) > butane (AC4) > pentane (AC5). The determination coefficient between the saturated hydrocarbon indicators exceeds 0.9, indicating that these components have the same source. Data analysis reveals that the genetic type of hydrocarbon gases in the study area is generally thermogenic, with limited microbial contribution to saturated hydrocarbons, indicating deep oil and gas characteristics. The coincidence between the anomalous areas and geological structures indicates that the distribution of these anomalies is closely related to fault distribution.